(untitled) (Research, Society and Development, 2021)
Himatanthus obovatus, known as janaguba, is found in Northeastern Brazil. Its leaves are used for hypertension, skin blemishes and as an anti-tumor, however studies regarding its healing action are still incipient. The study aimed to analyze the phytochemical profile and the healing effect of the ethanol extract of H. obovatus leaves in mice. The phytochemical prospection of the extract was carried out by the colorimetric test. The gels (carbopol plus the extract) were made with doses of 50, 75 and 100 mg/kg. Carbopol, distilled water, Nebacetin® ointment and extract (gel) were applied topically to the area of the mice lesion as negative control (NC), solvent (SC), positive (PC) and treatment group, respectively, for 21 days. Wounds were recorded on days 0, 7, 14 and 21 days for macroscopic and histological analysis after 21 days. Data were analyzed using the Kruskal-Wallis or Tukey test (p < 0.05). The results showed the presence of tannins, reducing sugars, phenols, flavonoids and alkaloids. In the intergroup, the extract did not show significant difference in the area of the lesion when compared to the PC after the 14th (50 and 75 mg/kg) and 21st days for all doses. In the intragroup, all doses of extract showed a reduction after the 14th and 21st to 100 mg/kg. The extract showed a significant increase in fibroblasts and collagen area at 50 and 100 mg/kg. Thus, the extract has the potential to be explored as an herbal medicine that can be used as a healing gel.